2012
DOI: 10.1038/tpj.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral expression profiling of genes involved in angiogenesis in colorectal cancer patients treated with chemotherapy plus the VEGFR inhibitor PTK787/ZK 222584 (vatalanib)

Abstract: The phase III CONFIRM clinical trials demonstrated that metastatic colorectal cancer patients with elevated serum lactate dehydrogenase (LDH) had improved outcome when the vascular endothelial growth factor receptor (VEGFR) inhibitor PTK/ZK (Vatalanib) was added to FOLFOX4 chemotherapy. We investigated the hypothesis that high intratumoral expression of genes regulated by hypoxia-inducible factor-1 alpha (HIF1α), namely LDHA, glucose transporter-1 (GLUT-1), VEGFA, VEGFR1, and VEGFR2, were predictive of outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…We then examined associations between CTC gene expression levels and outcomes. We used the optimal cut‐off value method as previously described . The cut‐off value of 0.05 for EGFR expression at baseline was chosen based on the maximum χ 2 approach.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined associations between CTC gene expression levels and outcomes. We used the optimal cut‐off value method as previously described . The cut‐off value of 0.05 for EGFR expression at baseline was chosen based on the maximum χ 2 approach.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells were collected using laser-capture micro-dissection as described recently [24]. In short, three sections, each of 10-um thickness, were dewaxed, re-hydrated and stained with nuclear fast red (American Master Tech Scientific, Lodi, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A phase I dose‐escalation study of patients with metastasized colorectal cancer showed the typical side effects, such as hypertension, with a maximal dose of 1250 mg/day in combination with FOLFOX4 chemotherapy . Intratumor profiling of gene expression revealed that the up‐regulation of the expression of angiogenesis‐associated genes ( e.g., Glut‐1, VEGFR‐1/‐2 and HIF‐1α) and of microvessel density predicted the outcome to antiangiogenic therapy in patients with colorectal cancer. Unfortunately, in a recently published phase III trial that included 855 patients, no significant extension of OS was observed in patients treated with Vatalanib combined with FOLFOX4 compared with the placebo group.…”
Section: Biological Basis Of Receptor Tyrosine Kinases (Rtk) Inhibitimentioning
confidence: 99%